LEGAL PROTECTION FOR CUSTOMERS USING E-BANKING SERVICES FROM THE THREAT OF CYBER CRIME (CASE STUDY AT PT BANK RAKYAT INDONESIA, SIMPANG TIGA UNIT, SIMPANG EMPAT BRANCH, WEST PASAMAN) - Ahmad Sukri; Nur Asmah; Hardimen, Hardimen (Journal of Social and Economics Research, 2025)
The majority of banks have provided e-banking services that make it easier for customers to transact anytime and anywhere, but these services also carry the risk of cybercrime such as fraud in the name of the bank. This study aims to analyze legal protection for customers using e-banking and the bank's responsibility in the event of losses at PT BRI Unit Simpang Tiga Simpang Empat Branch, West Pasaman. The method used is empirical juridical through a legislative approach, document study, and interviews. The results of the study indicate that the implementation of the banking system refers to applicable regulations, and the bank is responsible for processing customer transactions and complaints, although there are still delays in follow-up information. The bank provides full compensation if the loss is caused by a system error or internal negligence, but does not compensate for losses caused by customer negligence, although it still provides assistance such as transaction tracking, information, and assistance to the authorities.